Efektivitas Pembelajaran PAK Dengan Metode Bercerita Berbantuan Wayang Kulit Kelas 12 SMA Tarakanita Magelang - Florentius Berlin Bena Putra; FR. Wuriningsih; Yustinus Joko Wahyu Yuniarto (CV. Alim's Publishing, 2023)
From the results of interviews conducted with teachers in Catholic religious learning, there was a problem that class 12 students at SMA Tarakanita Magelang felt lazy and bored, only 42 students reached Standard of minimum 76. Can the storytelling method assisted by shadow puppets increase student motivation and achievement. Through quantitative research with observation instruments, questionnaires, questions and using the help of the SPSS application. The results obtained from this study indicate the effect of learning motivation in the form of student independence motivation given to the wayang kulit assisted storytelling method, namely an average score of 40 which is considered dominant for the results of student independence motivation, and the influence of learning independence obtained is also strengthened by student achievement where the experimental class got an average score of 86 while the control class used the tachered centered method where the teacher only read the material without only getting an average score of 78. The responses given by the experimental class also showed their interest in learning to use the wayang kulit assisted storytelling method as evidenced by the average score the average obtained was 41 for Catholic religious education lessons. Based on the results that have been obtained, it can be concluded that the use of wayang kulit-assisted storytelling methods influences learning motivation and in turn is effective in increasing student motivation and achievement in Catholic religious education lessons on Diversity Material as the Original Reality of Life at Tarakanita High School Magelang.